Research in personnel and human resources management - Buckley, M. Ronald; Wheeler, Anthony R.; Baur, John E.; Halbesleben, Jonathon R. B. (Research in personnel and human resources management, 2024)
Volume 42 of Research in Personnel and Human Resources Management offers several original scholarly contributions written by thought leaders in the field of human resources management. Featuring the latest research on novel, emerging areas of HRM, chapters explore metacognition, the role of HR in compensation, real options perspectives, female CEO leadership, corporate social responsibility, a theoretical model of the patriotic organization, and the use of unmeasured latent method factors.